(untitled) (Praxis Educativa, 2023)
This article presents dimensions of analysis that became the object of reflection of the teaching practices developed, in the context of pandemic during the years 2020 and 2021, by the students of the career of Teacher training on biological science at UNC. For this purpose, a documentary study was carried out, taking as objects of analysis the reports that the students wrote about their residencies carried out at the higher level and in high school. In the study, categories derived from theoretical references together with new emerging aspects were identified, new dimensions were constructed and, finally, a re-analysis and coding was made taking as reference the new constructed categories. The main results indicate that the students were able to question and challenge their own decisions applying the new meanings that were built from the challenges posed during the practices.